Evaluation of N-NOSE as a surveillance tool for recurrence in gastric and esophageal cancers: a prospective cohort study - Sayuri Iitaka; Akihiro Kuroda; Tomonori Narita; Hideyuki Hatakeyama; Masayo Morishita; Umbhorn Ungkulpasvich; Takaaki Hirotsu; Eric di Luccio; Koichi Yagi; Yasuyuki Seto (BMC Cancer)
Abstract Objective Early detection of recurrent gastric and esophageal cancers remains a critical challenge. Innovative and non-invasive cancer screening technologies, such as N-NOSE, can improve early detection. N-NOSE is a urine-based scent test that leverages the olfactory abilities of the nematode C. elegans. For the first time, this prospective study evaluates the efficacy of the N-NOSE chemotaxis index as a novel biomarker for postoperative surveillance and recurrence in patients with upper gastrointestinal cancers. Methods A two-year prospective cohort study was conducted at The University of Tokyo Hospital, involving 40 patients with gastric and esophageal cancers. Urine samples were collected pre- and postoperatively and analysed using the N-NOSE technique. Results In cases of recurrence with vascular invasion, the chemotaxis index at 100-fold urine dilution was significantly elevated compared to the non-recurrence group. Conclusion This study suggests the potential of N-NOSE as an effective follow-up tool for patients with upper gastrointestinal cancer, particularly those with vascular invasion. While N-NOSE has been validated to distinguish between cancer and non-cancer, and its performance compared to traditional markers has been proven, it has not been studied for recurrence. Our data highlights, for the first time, the capability of N-NOSE in the surveillance of cancer recurrence.